Single crystalline quaternary sulfide nanobelts for efficient solar-to-hydrogen conversion - Wu, Liang; Wang, Qian; Zhuang, Tao-Tao; Li, Yi; Zhang, Guozhen; Liu, Guo-Qiang; Fan, Feng-Jia; Shi, Lei; Yu, Shu-Hong (Nature communications, 2020)
Although solar-driven water splitting on semiconductor photocatalysts is an attractive route for hydrogen generation, there is a lack of excellent photocatalysts with high visible light activity. Due to their tunable bandgaps suitable for superior visible-light absorption, copper-based quaternary sulfides have been the important candidates. Here, we first assessed the preferred facet of wurtzite Cu-Zn-In-S for photocatalytic hydrogen evolution reaction using the relevant Gibbs free energies determined by first principle calculation. We then developed a colloidal method to synthesize single crystalline wurtzite Cu-Zn-In-S nanobelts (NBs) exposing (0001) facet with the lowest reaction Gibbs energy, as well as Cu-Zn-Ga-S NBs exposing (0001) facet. The obtained single crystalline Cu-Zn-In-S and Cu-Zn-Ga-S NBs exhibit superior hydrogen production activities under visible-light irradiation, which is composition-dependent. Our protocol represents an alternative surface engineering approach to realize efficient solar-to-chemical conversion of single crystalline copper-based multinary chalcogenides. Quaternary sulfides are important candidates for solar-to-H 2 conversion due to tunable bandgaps for controllable light absorption. Here, authors prepare single crystalline wurtzite Cu-Zn-In-S and Cu-Zn-Ga-S nanobelts with (0001) facets that show strong photocatalytic H 2 production performances.